Optional subject “Intelligent technologies in warfare” instructional features - Pincevičius, Albertas; Bekešienė, Svajonė (Lietuvos matematikos rinkinys, 2013)
Make use of the computer algebra package MAPLE and Geographic Information Systems (GIS) databases. Offered information system, which can simulate a military unit steps and the capacity to carry out the task and display the results of digital experiments on a map. Use Monte Carlo method for simulating the individual soldier’s actions on the battlefield, assess the influence of random factors. The artillery impact assessed carried out and the results displayed on the digital map. It is proposed psychological testing program. With this program is possible determined professional purposefulness, of the organizational and communication skills, leadership, and other personal characteristics of the soldiers.
Keywords: modeling of warfare; psychological testing; a stochastic model; Geographic Information System